Improving students’ reading comprehension ability using task based language teaching - Ruslina Tri Astuti (Universitas Negeri Yogyakarta, 2020)
This study was conducted in response to the fact that the students’ reading comprehension ability was much lower than they should have achieved. It was caused by several reasons, one of themwas related to the poor teaching learning process. In this study, Task-based Language Teaching (TBLT) was used to improve the teaching learning process and the students’ reading comprehension ability. This research was a Classroom Action Research (CAR) study and it was done in two cycles. Observation and interviews were used to collect data which were then analyzed qualitatively. Students’ achievement of daily-test, the students’ self reflection in the form of rating format and the students’ achievement of post-tests were used in order to support the data collected. The results of this study indicate that TBLT can improve not only the teaching learning process but also the class 8D of MTsN Yogyakarta II students’ reading comprehension ability in recount text. It is shown that the students are interested to learn reading and they enjoy the reading teaching learning process using TBLT. The students’ average score before the action is 62.81. In the first cycle the mean score is 72.03, meanwhile the mean score in the second cycle is 79.06. It means that there is an improvement of students’ scores from cycle to cycle.